Cerambyx cerdo and Cerambyx welensii Oak-Living Sympatric Populations Exhibit Species-Specific Responses to Face Ecological Factors in the Wild - Luis M. Torres-Vila; F. Javier Mendiola-Díaz; Tara Canelo (Diversity, 2023)
Oak open woodlands (dehesas) have outstanding socioeconomic and ecological values, sustain traditional agro-silvo-pastoral uses, provide high-value ecosystem services, and constitute key biodiversity hotspots. Cerambyx cerdo and Cerambyx welensii are two large, oak-living, wood-boring, sympatric longhorn beetles (Coleoptera: Cerambycidae) that may reach pest status in SW Spain, contributing to oak decline. Understanding species-specific habitat requirements determining occupancy–abundance patterns is needed to develop management or control strategies. We conducted a large-scale, four-year study using 1650 feeding traps to ascertain longhorn abundance and species-specific habitat suitability in relation to 18 ecological variables, 9 biotic (oak species, forest mass, trunk diameter, tree density, basal area, forest cover, shrub cover, ground cover, oak renewal), and 9 abiotic (bedrock outcrops, altitude, ground slope, aspect, mean temperature: annual/July/January, annual precipitation, insolation). Results showed that longhorn abundance was sensitive to most ecological variables and to many interactions between them. Interestingly, interactions between ecological variables and longhorn species were widespread, signifying that responses were species-specific and therefore predictive Generalized Linear Mixed Models (GLMMs) were different between species. Our research contributes to the understanding of the ecological factors that shape longhorn species-specific occupancy–abundance patterns, delves into their sympatric relationship, and contributes toward improving sustainable forest practices that will mitigate longhorn impact in oak open forests.